Information Complexity of Multidimensional Fredholm Integral Equations with Harmonic Coefficients - Azizov, M. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For the class of multidimensional Fredholm integral equations with free terms and kernels periodic and harmonic in each variable, we determine the exact order of the minimum radius of information in the logarithmic scale.